Pengaruh Herbisida Glifosat 480 SL, Paraquat dan Kombinasinya pada Gulma Pakisan (Nephrolepis biserrata) di Kebun Kelapa Sawit Menghasilkan - Joko Prianto; Yusmaidar Sepriani; Dini Hariyati Adam; Widya Lestari (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
In this study, weeds in oil palm plantations that produce, including Nephrolepis biserrata, have different resistance to single or combination herbicides, with a mixed herbicide of glyphosate 480 sl and paraquat is expected to control fern weeds (Nephrolepis biserrata) more effectively and efficiently than singly. carried out using a non-factorial randomized block design (RAK) with 3 treatments, namely, D0: Babat D1: glyphosate herbicide 480 sl dose 30 ml 5 liter water volume, D2: paraquat herbicide 25 ml 5 liter water volume, D3: glyphosate herbicide 480 sl + herbicide paraquat at a dose of 20 ml with a volume of 5 liters of water added with mechanical treatment repeated 4 times. Observation parameters in this study were weed mortality rate, leaf color poisoning rate and natality. The results showed that the best treatment was to use the herbicide paraquat (25 ml volume of water 5 liters) on day 13 the weeds had died, while in the herbicide treatment glyphosate 480 sl (30 ml volume of water 5 liters) suppressed weed death on day 19 in the herbicide treatment glyphosate 480 sl mixed with paraquat was able to suppress mortality on day 19 Keywords: plantation, weeds, herbicides